Guiding Employees in Disruption-led Uncertainty - The role of Leaders and Approaches to Support Them - Schmitt, Judith; Pauknerová, Daniela, 1970-; Orel, Marko, 1986-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
In today’s dynamic global landscape, organisations face with challenges from economic volatility, political unrest, and technological advancements (World Health Organization & International Labour Organization, 2022). This convergence leads to a ‘polycrisis,’ with multiple disruptive events occurring (World Economic Forum, 2023). In the working world, this causes pervasive uncertainty, permeating organisational structures and profoundly affecting employee well-being (Ngirande, 2021). Organisational uncertainty presents diverse challenges. Leaders play a crucial role in navigating these by fostering adaptive behaviours (Bennett et al., 2016), enabling effective responses and promoting well-being. Leadership development becomes a priority, equipping leaders to navigate uncertainty (Nöthel et al., 2023), fostering resilience and facilitating smoother transitions during upheaval. Accurate evaluation of leadership interventions is crucial, ensuring that effective strategies meet evolving needs (Nielsen & Randall, 2013). In this thesis, I present three articles addressing this scenario, developed from my PhD research: Article One: Schmitt, J. (2024). Employee Wellbeing and the Remote Leader – A Systematic Literature Review. Central European Business Review. DOI: 10.18267/j.cebr.352 Article Two: Schmitt, J., Vasquez, C., Pauknerova, D. (under review). Guiding Through Turbulent Times: Coaching During Merger and Acquisition. Journal of Change Management. Article Three: Schmitt, J., Nielsen, K., Axtell, C., Vasquez, C. (under review). Every Cloud Has a Silver Lining - Workplace Interventions for Leaders in Times of Uncertainty. International Journal of Workplace Health Management. This thesis is organised in the following way: I first present my research’s theoretical background, emphasising the significance of the problem I aim to address.
Drawing on this, I formulate the objective of this research and state the research questions of each of the three articles. Next, I briefly summarise the three articles, followed by a chapter on their methodology. Lastly, I discuss the findings and conclude by considering strengths, limitations, and directions for future research.
Vedoucí práce: Daniela Pauknerová
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management and managerial economics [obor disert. práce]; disertace; dissertations